Redefining Tumor-Associated Macrophage Subpopulations and Functions in the Tumor Microenvironment - Wu, Kaiyue; Lin, Kangjia; Li, Xiaoyan; Yuan, Xiangliang; Xu, Peiqing; Ni, Peihua; Xu, Dakang (Frontiers in Immunology, 2020)
The immunosuppressive status of the tumour microenvironment (TME) remains poorly defined due to a lack of understanding regarding the function of tumour-associated macrophages (TAMs), which are abundant in the TME. TAMs are crucial drivers of tumour progression, metastasis and resistance to therapy. Intra- and inter-tumoural spatial heterogeneities are potential keys to understanding the relationships between subpopulations of TAMs and their functions. Antitumour M1-like and pro-tumour M2-like TAMs coexist within tumours, and the opposing effects of these M1/M2 subpopulations on tumours directly impact current strategies to improve antitumour immune responses. Recent studies have found significant differences among monocytes or macrophages from distinct tumours, and other investigations have explored the existence of diverse TAM subsets at the molecular level. In this review, we discuss emerging evidence highlighting the redefinition of TAM subpopulations and functions in the TME and the possibility of separating macrophage subsets with distinct functions into antitumour M1-like and pro-tumour M2-like TAMs during the development of tumours. Such redefinition may relate to the differential cellular origin and monocyte and macrophage plasticity or heterogeneity of TAMs, which all potentially impact macrophage biomarkers and our understanding of how the phenotypes of TAMs are dictated by their ontogeny, activation status and localization. Therefore, the detailed landscape of TAMs must be deciphered with the integration of new technologies, such as multiplexed immunohistochemistry (mIHC), mass cytometry by time-of-flight (CyTOF), single-cell RNA-seq (scRNA-seq), spatial transcriptomics and systems biology approaches, for analyses of the TME.